Visual Merchandising Impact on Consumer Attention: A Qualitative Retail Study - Ayudia, Kirana (Omnia Tempus, 2025)
This research aims to investigate the influence of store environment and design on consumer behavior, focusing on how various elements such as visual merchandising, store layout, and environmental cues affect customer perceptions, decision-making, and overall satisfaction. The study employs a qualitative research methodology, relying on a comprehensive review of literature and case studies from retail and marketing disciplines. The study finds that store environment factors like lighting, color, and spatial design significantly influence customers' quality inferences and store image, ultimately shaping their shopping experience and purchase intentions. It also reveals that strategic store layouts and the integration of entertainment elements into retail spaces enhance customer engagement and satisfaction. Additionally, the research highlights the role of environmental cues in reinforcing brand identity and emotional connections with customers. The findings suggest that retailers must carefully design their store environments to align with consumer expectations and to foster a positive shopping experience. This research contributes to the existing body of knowledge by emphasizing the importance of environmental design in retail marketing and offering practical insights for retail managers and marketers to improve consumer engagement and loyalty.